Penggunaan pestisida oleh petani tanaman pangan di Propinsi Jawa Tengah dan Daerah Istimewa Yogyakarta pada tahun 1989. Pesticide use by food crops farmers in Central Java and Yogyakarta Special Region Provinces ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
A farmers survey on pesticide use was conducted in 10 regencies at two provinces, Central Java and Yogyakarta Special Region in January 1990. A total of 295 respondents. were taken, and they were grouped according to their respective crops, namely rice, secondary crops, lowland vegetables and upland vegetables. Questions on pesticides, pesticide use and related subjects were forwarded to those respondents. Farmers knowledge on various species of pests and diseases